Feminist perspectives on environmental justice and health in Jamaica - Albarus, Neena; Lue, J’Anna-Mare; Kerrison, Erin; Carrasquillo, Maya (Frontiers in Sociology, 2024)
Jamaica is an island nation with a history that is informed by Taino settlement, European colonisation, chattel slavery, disinvestment, and continued extractivism. This perspective paper leverages a historical analysis to explore environmental injustices affecting the health and quality of life of Jamaicans living in Jamaica. This article hopes to contribute to a growing but limited body of scholarly research that contends with environmental and climate justice in the context of the Caribbean. In discussing a lack of critical environmental infrastructure, such as reliable solid waste management, and the impacts of extractive industries, such as bauxite mining, the paper intends to highlight the environmental, public health, and social harms that are produced. Employing an intersectional approach grounded in Black feminist epistemology put forward by Patricia Hill Collins, the authors use their lived experiences as a source of knowledge. The paper analyses how these environmental injustices harm Jamaican communities at large but underscores the compounded challenges faced by Jamaican women who experience marginalisation on the basis of gender, urban/rural residency, and class. The paper concludes by urging researchers, policymakers, regulatory bodies, and other stakeholders to conduct further research and create sustainable and equitable environmental standards that have considerations for environmental injustice in Jamaica.